Significados acerca do HIV e sexualidade das pessoas idosas participantes da campanha fique sabendo 2015 em Peruíbe-SP - Vieira, Valeria De Angelis [UNIFESP] (2018)
Aging, Both In Brazil And In Many Other Countries, Is An Undeniable Fact. Today, People Aged 60 And Over Represent 10.8% Of The Brazilian Population, Corresponding To 20.5 Million People. This Reality Generated The Need To Create Public Policies That Would Guarantee Rights And Improve The Quality Of Life, Through Social And Health Actions, For This Population. These Actions Contributed To The Longevity Of These Individuals And, Consequently, To Greater Socialization, Increasing The Possibilities Of Experiencing New Experiences. Some Research Points To A Growth Of People 60 Years Of Age Or Older Living With Hiv / Aids, Which May Be Signaling The Need For Aspects Related To Sexuality And Prevention To Be Focused On This Age Group. In This Qualitative Study, The Objective Was To Understand The Meanings About Hiv / Aids Among The Elderly Population That Participated In The 2015 Fique Sabendo (Get To Know) Campaign In The City Of Peruíbe And To Capture The Notions About Sexuality And Sexual Health In This Life Cyc